Case report: Successful treatment of advanced colon cancer in an eighty-year-old man with long-term and multi-stage endoscopic minimally invasive therapy - Zhang, Nana; Zhu, Lulu; Liu, Yan; Chen, Xiaolong; Zhang, Bifang; Wen, Chunhong; Zhang, Huayu; Tang, Qinglin; Zhang, Mingqing (Frontiers in Oncology, 2024)
Background: No previous studies have reported on the use of minimally invasive endoscopic therapy for colon cancer in older patients. Case Presentation: An 80-year-old man was admitted to our hospital with haematochezia and diagnosed with advanced colon cancer in 2018. Traditional surgical care was rejected by his family. We successfully treated the patient with multiple minimally invasive endoscopic therapies, such as argon plasma coagulation, from 2018 to 2021. Conclusion: Invasive endoscopic therapy is a feasible way to treat colon cancer in older patients.